KEPATUHAN WAJIB PAJAK TERHADAP PERATURAN PEMERINTAH NOMOR 23 TAHUN 2018 TENTANG PAJAK PENGHASILAN SEBELUM DAN SESUDAH DIBERLAKUKANNYA PERATURAN MENTERI KEUANGAN NOMOR 44 TAHUN 2020 TENTANG INSENTIF PAJAK UMKM - Veri Dwi Pratiwi; Anik Malikah; Junaidi Junaidi (Universitas Islam Malang, 2022)
This study aims to empirically prove whether there is a difference or not, taxpayer compliance with Government Regulation Number 23 of 2018 before and after the enactment of PMK Number 44 of 2020 UMKM incentives based on new income and taxpayers. The research method used in this research is to use a comparative case study approach (Comparative Research). This research is a quantitative research. Data collection for this study used the documentation method available at KPP Pratama North Malang. The data analysis method used in this study used descriptive statistical data analysis techniques, normality test and paired sample t-test. The results of this study indicate that based on descriptive statistics the value of Tax Revenue Based on Incentives before the implementation of PMK 44 in 2020 is higher with an average value of 103294068.13 compared to Tax Revenue Based on Incentives after the implementation of PMK 44 in 2020 which is 47388064,473. Meanwhile, based on descriptive statistics, the value of Tax Revenue Based on new taxpayers before the implementation of PMK 44 in 2020 was higher with an average value of 15.0909 compared to Tax Revenue Based on new taxpayers after the implementation of PMK 44 in 2020, which was 2.7818.Keywords: Taxpayer Compliance, PP 23 of 2018, PMK 44 of 2020 Incentives for UMKM.